Acid-tolerant cyclodextrin-based ruthenium nanoparticles for the hydrogenation of unsaturated compounds in water. Issue 24 (13th November 2017) - Noël, Sébastien; Bourbiaux, Dolorès; Tabary, Nicolas; Ponchel, Anne; Martel, Bernard; Monflier, Eric; Léger, Bastien
Abstract : Ru NPs, stabilized by a water soluble cationic β-cyclodextrin polymer, proved to be efficient for the hydrogenation of acid substrates. Abstract : A water-soluble β-cyclodextrin polymer synthesized by crosslinking β-cyclodextrin with epichlorohydrin and glycidyltrimethylammonium chloride allowed the stabilization of ruthenium nanoparticles not only in basic aqueous medium but also in acidic medium. The aqueous ruthenium colloidal suspensions obtained with this polymer were active as catalysts for the hydrogenation of a large variety of unsaturated compounds including aromatic or fatty acids. The recycling of this catalytic system was attested through ten consecutive runs without loss of stability and activity, demonstrating its robustness.